Proteasome-Mediated Regulation of Cdhr1a by Siah1 Modulates Photoreceptor Development and Survival in Zebrafish - Piedade, Warlen Pereira; Titialii-Torres, Kayla; Morris, Ann C.; Famulski, Jakub K. (Frontiers in Cell and Developmental Biology, 2020)
Congenital retinal dystrophies are a major cause of unpreventable and incurable blindness worldwide. Mutations in CDHR1, a retina specific cadherin, are associated with cone-rod dystrophy. The ubiquitin proteasome system (UPS) is responsible for mediating orderly and precise targeting of protein degradation to maintain biological homeostasis and coordinate proper development, including retinal development. Recently, our lab uncovered that the seven in absentia (Siah) family of E3 ubiquitin ligases play a role in optic fissure fusion and identified Cdhr1a as a potential target of Siah. Using two-color whole mount in situ hybridization and immunohistochemistry, we detected siah1 and cdhr1a co-expression as well as protein localization in the retinal outer nuclear layer (ONL), and more precisely in the connecting cilium of rods and cones between 3-5 days post fertilization (dpf). We confirmed that Siah1 targets Cdhr1a for proteasomal degradation by co-transfection and co-immunoprecipitation in cell culture. To analyze the functional importance of this interaction, we created two transgenic zebrafish lines that express siah1 or an inactive siah1 (siah1RING) under the control of the heat shock promoter to modulate Siah activity during photoreceptor development. Overexpression of siah1, but not siah1RING, resulted in a decrease in the number of rods and cones at 72 hours post fertilization (hpf). The number of retinal ganglion cells, amacrine and bipolar cells was not affected by Siah1 overexpression, and there was no significant reduction of proliferating cells in the Siah1 overexpressing retina. We did however detect increased cell death, confirmed by an increase in the number of TUNEL+ cells in the ONL, which was proteasome-dependent, as proteasome inhibition rescued the cell death phenotype. Furthermore, reduction in rods and cones resulting from increased Siah1 expression was rescued by injection of cdhr1a mRNA, and to an even greater extent by injection of a Siah1-insensitive cdhr1a variant mRNA. Lastly, CRISPR induced loss of Cdhr1a function phenocopied Siah1 overexpression resulting in a significant reduction of rods and cones. Taken together, our work provides the first evidence that Cdhr1a plays a role during early photoreceptor development and that Cdhr1a is regulated by Siah1 via the UPS.